arrow_back Differentiate the function $m=\frac{3}{2} n^{4}-1$

12 views
Differentiate the function $m=\frac{3}{2} n^{4}-1$

$\dfrac{d m}{d n}=\frac{3}{2}\left(4 n^{3}\right)-0=6 n^{3}$
by Platinum
(106,910 points)

Related questions

1 answer 60 views
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
If $\left(2 x^{2}-x-3\right)$ is a factor of $f(x)=2 x^{3}-5 x^{2}-x+6$, find the other factor
1 answer 36 views
If $\left(2 x^{2}-x-3\right)$ is a factor of $f(x)=2 x^{3}-5 x^{2}-x+6$, find the other factorIf $\left(2 x^{2}-x-3\right)$ is a factor of $f(x)=2 x^{3}-5 x^{2}-x+6$, find the other factor A. $(x-2)$ B. $(x-1)$ C. $(x+1)$ D. $\left( ... close Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993 How would you solve \(\frac{x^{2}}{5}\left(5-\frac{5}{x}\right)=6 ?$
1 answer 35 views
How would you solve $\frac{x^{2}}{5}\left(5-\frac{5}{x}\right)=6 ?$How would you solve $\frac{x^{2}}{5}\left(5-\frac{5}{x}\right)=6 ?$ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
If $(x+1)$ and $(x-2)$ are factors of the polynomial $g(x)=x^{4}+a x^{3}+b x^{2}-16 x-12$, find the values of $a$ and $b$.
1 answer 41 views
If $(x+1)$ and $(x-2)$ are factors of the polynomial $g(x)=x^{4}+a x^{3}+b x^{2}-16 x-12$, find the values of $a$ and $b$.If $(x+1)$ and $(x-2)$ are factors of the polynomial $g(x)=x^{4}+a x^{3}+b x^{2}-16 x-12$, find the values of $a$ and $b$. ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Solve: $2^{2 x+1}-5\left(2^{x}\right)-12=0$
1 answer 19 views
Solve: $2^{2 x+1}-5\left(2^{x}\right)-12=0$Solve: \ 2^{2 x+1}-5\left(2^{x}\right)-12=0 \ ...
close

Notice: Undefined index: avatar in /home/customer/www/mathsgee.com/public_html/qa-theme/AVEN/qa-theme.php on line 993
Differentiate $g(t)=4(t+1)^{2}(t-3)$ with respect to $t$
1 answer 7 views
Differentiate $g(t)=4(t+1)^{2}(t-3)$ with respect to $t$Differentiate &nbsp;$g(t)=4(t+1)^{2}(t-3)$ with respect to $t$ ...
close
0 answers 70 views
Perform the indicated operations. Write each answer using only positive exponents. Assume all variables represent positive real numbers. $$\frac{9 m^{1 / 2} n^{3 / 2}}{m^{-7} n\left(m^{3} n\right)^{1 / 2}}$$Perform the indicated operations. Write each answer using only positive exponents. Assume all variables represent positive real numbers.  \frac{9 m^ ...
close